The Degree of Availability of the Science, Technology, Society and Environment (STSE) approach in science curricula in the Sultanate of Oman - Al-Rumhi, Humood Sulieman Saif; Al-Badri, Ahmed Humaid Mohammed (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the degree of availability of the science, technology, society and environment (STSE) approach in the science curricula of the Cambridge International Series applied in the second cycle of basic education in the Sultanate of Oman, and the extent to which this degree differs between grades. The study sample consisted of science curricula for grades 8-5, which were determined For students of basic education for the academic year 2021/2022, and to answer the questions of the study, the researcher used the analytical method, and prepared a content analysis card, which in its final form consisted of (30) indicators distributed over six main areas of science, technology, society and the environment, which are The positive effects of science and technology on society and the environment, the negative effects of science and technology on society and the environment, the impact of society on science and technology, the impact of science and technology on solving environmental problems, the interrelationships between science and technology, and the determinants of both science and technology, and the subject (the lesson) was adopted as a unit of analysis. To verify the validity of the tool, it was presented to a number of specialized arbitrators, and its stability was done by calculating the reliability coefficient of " Holisti ", among three analysts for a sample of the topics of the analyzed curricula, and the results revealed: availability of the trend (16.3%), which is considered a weak percentage, due to the importance of the educational orientation and its being one of the dimensions of scientific culture. It also revealed the uneven distribution of the orientation fields in the curricula of the sample classes, and the presence of statistical significance confirming the difference in the availability of the orientation in the curricula of the analyzed classes. In light of these results, the study recommended the importance of including the orientation fields and its indicators when developing science curricula for basic education stages, and distributing its availability in a comprehensive and balanced manner in science curricula topics.